Technical performance and perceived exertion variations between small-sided basketball games in under-14 and under-16 competitive levels - Clemente, F. M.; Sanches, R.; Moleiro, C. F.; Gomes, M.; Lima, R. (Journal of Human Kinetics, 2020)
The aim of this study was twofold: i) to compare the rate of perceived exertion (RPE) and the frequencies of technical actions per minute in different small-sided games (SSGs) between under-14 and under-16 age groups, and ii) to compare the RPE and the frequencies of technical actions per minute between 1 x 1, 2 x 2, 3 x 3, 4 x 4 and 5 x 5 formats within age groups. Twenty young male basketball players from the same club (N = 10, from under-14; N = 10, from under-16) competing at the national level voluntarily participated in this study. Five different SSGs (1 x 1, 2 x 2, 3 x 3, 4 x 4 and 5 x 5) were played twice on courts of the same relative area and were compared in terms of the RPE and technical actions. The number of technical-tactical actions per minute, i.e. conquered balls (CB), received balls (RB), lost balls (LB), attacking balls/passes (AB), shots (S), rebounds (R), and the RPE were collected for each player for each SSG session. The results revealed that most of the differences between age groups were considered trivial/small and/or unclear for all SSG formats, though likely moderate differences between age groups were found in 1 x 1 and 2 x 2 SSGs, revealing that young players had greater frequencies of received, conquered, and lost balls. Within-age-group comparisons also showed moderate-to-large increases in technical actions during smaller formats than during larger ones. The main evidence of this study revealed that age group seemed not to largely influence the RPE or technical actions during different SSGs. However, smaller formats moderately-to-largely increased the number of technical actions. Interestingly, the biggest format (5 x 5) largely increased the RPE in comparison to the remaining formats. As a conclusion, technical actions and the RPE were influenced more by the format of play than by the age group.